Sistem Informasi Anggaran Biaya Pemeliharaan, Kerusakan Dan Konstruksi Pada Bagian Administrasi - Oji Tiongkos Maruli Chrismas; Asep Ririh Riswaya; Fikri Irawan Abdurahman (Acman: Accounting and Management Journal, 2022)
Maintenance and Construction of West Bandung Witel is one of the work units of PT. Telkom Akses Jawa Barat, whose job is to build and maintain the broadband network owned by PT. Telkom Indonesia which is located in Dayeuh Kolot, Bandung City. In improving performance and activities within the Construction and Maintenance Unit environment, a system or application is needed that can facilitate work data collection. So that the work carried out by the unit can be recorded properly and on time according to the targets set by the company. Based on these problems, with this practical work a web-based system or application is built that can help with existing problems. Making this information system is done by way of data collection, analysis, design, implementation up to testing the information system. The end result of this research is a Maintenance and Construction Administration Information System that can be used to facilitate staff or employees in processing work data. Keywords : Administrative Information Systems, web, PHP, Laravel Framework